Mafia the history of the Mob in America - Osterlund, David; Royle, David; Kurtis, Bill; Gray, Edward (Edward S.); Meyer, David (Film producer); Cascio, Michael, 1950-; Fox, Stephen R.; Osterlund Company; Arts and Entertainment Network; New Video Group (New York A & E Television Networks, 2001)
This collection of documentaries produced by A & E presents a broad overview of organized crime in America, beginning with immigrants who formed gangs soon after arriving in the late 19th century. The focus is on Italian-American gangsters, though there are mentions of Irish and Jewish gangs, which at various times cooperated with or competed against the Mafia, and one program in the collection presents skeins of conjecture while seeking to document links between the Mob and the Kennedy political dynasty. The documentaries use vintage newsreel footage as well as clips of Hollywood versions of gang life to illustrate the narration.
(Disc 1) The Prohibition years/Birth of the American Mafia -- The Kennedys and the Mob -- (Disc 2) Unions and the Mob -- Empire of crime.
Title from container.
Standard version, full screen presentation.
"NTSC ; region 1"--Amazon.com.
Based on the book: Blood and power / by Stephen Fox.
Originally broadcast in 1993 as a series on the television program: "American Justice" ; original series title: "Target Mafia."
"Target Mafia" series producer, David Royle ; "Target Mafia" executive producer, David Osterlund ; "American justice" series executive producers, Bill Kurtis, Jonathan Towers ; A & E executive producer, Michael Cascio.
Keywords: 1900-1999; Organized crime -- United States -- History -- 20th century; Mafia -- United States -- History -- 20th century; Labor unions -- Corrupt practices -- History -- 20th century; Labor unions and communism -- History -- 20th century; Historical films; Documentary television programs; Documentary films; History